Political Bias and War - Jackson, Matthew O; Morelli, Massimo (American Economic Review, 2007)
We examine how countries' incentives to go to war depend on the “political bias” of their pivotal decision makers. This bias is measured by a decision maker's risk/reward ratio from a war compared to that of the country at large. If there is no political bias, then there are mutually acceptable transfers from one country to the other that will avoid a war in the presence of commitment or enforceability of peace treaties. There are cases with a strong enough bias on the part of one or both countries where war cannot be prevented by any transfer payments. Our results shed some new light on the uneven contender paradox and the interpretation of the “democratic peace.” We examine countries' choices of the bias of their leaders and show that when transfers are possible, at least one country will choose a biased leader, as that leads to a strong bargaining position and extraction of transfers. (JEL D72, D74)